Characteristics and outcome of pediatric non‐hodgkin lymphoma patients with ovarian infiltration at presentation. Issue 12 (19th July 2013) - van Dorp, Wendy; Owusuaa, Catherine; Laven, Joop S.E.; van den Heuvel‐Eibrink, Marry M.; Beishuizen, Auke
Abstract Background Ovarian infiltration in pediatric non‐Hodgkin lymphoma (NHL) at presentation is rare and information on outcome is scarce and mainly based on case reports and small series. Procedure Evaluation of clinical characteristics and outcome of ovarian infiltrated pediatric NHL cases of a single center, and an extensive review of the all cases reported so far in literature. Results At presentation, 6/60 female NHL cases of our center had ovarian infiltration, and combining these cases with earlier case reports, a total of 42 cases were identified. Median age at presentation was 10.9 years (range 0–18), and all but one had a B‐cell immunophenotype, with 32/42 cases being classified as Burkitt. Bilateral involvement was reported in 26/41 cases, of which 22 were bilaterally ovariectomized as first treatment. All cases were treated with chemotherapy. Relapses were reported in 9/36 and death in 16/36. After follow‐up in our center (median 13.4 years), in 2 cases anti‐Müllerian hormone (AMH) values were available (2.1 and 0.9 µg/L), in non‐ovarian cases median 2.2 µg/L. Conclusions We conclude that in case of ovarian tumors with negative markers, NHL should be considered in order to avoid unnecessary surgery. Pediatr Blood Cancer 2013;60:2054–2059. © 2013 Wiley Periodicals, Inc.